The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/2175-7860200960216
|View full text |Cite
|
Sign up to set email alerts
|

Redescoberta e tipificação de Octomeria leptophylla Barb. Rodr. (Orchidaceae), micro-orquídea endêmica de Minas Gerais, Brasil

Abstract: ABSTRACT(Rediscovery and typification of Octomeria leptophylla Barb. Rodr. (Orchidaceae), an endemic micro-orchid from Minas Gerais, Brazil) The rediscovery of Octomeria leptophylla, an endemic micro-orchid from Minas Gerais, Brazil thought to be extinct is presented. In 1877, João Barbosa Rodrigues described O. leptophylla based on a collection from "Serra de Caldas" (Municipality of Caldas), south of Minas Gerais. Since then, no other records were made either by herbarium botanists or private collector, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…Rodr. (Orchidaceae) é um exemplo cuja localidade-típica é a SPB, tendo sido considerada extinta por Biodiversitas (2007) e recentemente redescoberta (Menini Neto & Docha Neto 2009), embora não na SPB, mas em duas serras de municípios próximos, Andradas e Poços de Caldas, não tendo sido observada na área durante o presente estudo.…”
Section: Conservaçãounclassified
See 1 more Smart Citation
“…Rodr. (Orchidaceae) é um exemplo cuja localidade-típica é a SPB, tendo sido considerada extinta por Biodiversitas (2007) e recentemente redescoberta (Menini Neto & Docha Neto 2009), embora não na SPB, mas em duas serras de municípios próximos, Andradas e Poços de Caldas, não tendo sido observada na área durante o presente estudo.…”
Section: Conservaçãounclassified
“…O incentivo à pesquisa é essencial, devido ao incipiente conhecimento científico da região. Para conservar a biota local é necessário maior comprometimento das autoridades e maior fiscalização dos órgãos ambientais, uma vez que a região está inserida em uma Área de Proteção Ambiental que por definição é uma categoria de unidade de conservação com ocupação permitida, não apresentando assim, elevado poder de conservação (Menini Neto & Docha Neto 2009 …”
Section: Conservaçãounclassified
“…This subtribe is found in the Neotropics, from Argentina to southern Mexico. Micro-orchids in the Atlantic Forest in Brazil, which is home to a large number of micro-orchid endemic species and is one of the most threatened extinction biomes on the planet, face extreme extinction pressures with a reduction in the original habitat of over 90% [ 18 – 20 ]. Most species of Pleurothallidinae have no great commercial appeal, due to the small dimensions of the plants and their flowers, as well as the difficulties of cultivation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Micro-orchids in the Atlantic Forest in Brazil, which is home to a large number of micro-orchid endemic species and is one of the most threatened extinction biomes on the planet, face extreme extinction pressures with a reduction in the original habitat of over 90% [ 18 – 20 ]. Most species of Pleurothallidinae have no great commercial appeal, due to the small dimensions of the plants and their flowers, as well as the difficulties of cultivation [ 18 ]. There are few studies of asymbiotic germination of micro-orchids, which have shown low germination rates and slow growth of seedlings [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%